Pengaruh Model Project Based Learning Terhadap Berpikir Kritis dan Pemecahan Masalah Sumber Daya Alam IPS Sekolah Dasar - Lidyanti (CV. Akademi Merdeka, 2025)
This study investigates the effect of Project Based Learning (PjBL) on the critical thinking and problem-solving skills of fourth grade elementary school students in Social Studies, specifically on the topic of Natural Resources. A quantitative method with a descriptive-explanatory design was employed, involving 51 purposively selected students in Gunung Jati District. Data were collected using 20 essay items aligned with indicators of critical thinking and problem solving, which were validated (r_count > 0.361) and demonstrated high reliability (Cronbach's α = 0.899). Results of the paired sample t-test indicated a statistically significant improvement (p < 0.05) in students’ cognitive skills after the implementation of PjBL. The approach was particularly effective in enhancing students’ abilities to analyze problems, draw conclusions, and propose relevant solutions. These findings suggest that PjBL supports the development of higher-order thinking skills by engaging students in contextual, inquiry-based learning. However, challenges such as limited time and inadequate project resources were noted. Practically, the findings recommend integrating PjBL in Social Studies curricula to foster active and critical learning. Theoretically, the study reinforces constructivist learning principles as a basis for curriculum development in primary education.